2019
DOI: 10.7150/thno.38913
|View full text |Cite
|
Sign up to set email alerts
|

The use of micelles to deliver potential hedgehog pathway inhibitor for the treatment of liver fibrosis

Abstract: Rationale: Hedgehog (Hh) pathway plays an essential role in liver fibrosis by promoting the proliferation of hepatic stellate cells (HSCs) by enhancing their metabolism via yes-associated protein 1 (YAP1). Despite the presence of several inhibitors, Hh signaling cannot be controlled exclusively due to their poor efficacy and the lack of a suitable delivery system to the injury site. Therefore, it is rationale to develop new potent Hh inhibitors and suitable delivery carriers.Methods: Based on the structure and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…It has been demonstrated that HSCs are Hh responsive and will be transformed into fibrogenic myofibroblasts (MFs). However, HSC activation can be inhibited by interfering Hh signaling [67,68]. It is well-known that excessive autophagy and NLRP3 inflammasome activation can induce autophagic cell death and pyroptosis, respectively [69].…”
Section: Autophagy and Nlrp3 Inflammasomementioning
confidence: 99%
“…It has been demonstrated that HSCs are Hh responsive and will be transformed into fibrogenic myofibroblasts (MFs). However, HSC activation can be inhibited by interfering Hh signaling [67,68]. It is well-known that excessive autophagy and NLRP3 inflammasome activation can induce autophagic cell death and pyroptosis, respectively [69].…”
Section: Autophagy and Nlrp3 Inflammasomementioning
confidence: 99%
“…For instance, GANT-61 inhibited HH pathway members, GLI1 and GLI2 in HPV and KSHV associated tumors (Samarzija and Beard, 2012;Asha et al, 2020). Vismodegib, a SMO inhibitor that effectively terminates HH signaling, decreased liver fibrosis induced by HBV and HCV infection (Kumar et al, 2019). GSI repressed Notch signaling induced by KSHV, EBV, and HCV in associated diseases (Ito et al, 2011;Giunco et al, 2015;Jiang B.C.…”
Section: Hh Notch and Wnt Pathways: Intersection For Common Therapeutic Targetsmentioning
confidence: 99%
“…These are summarized in Table 4 . Like with liposomes, the majority of these utilize APIs loaded into a lipophilic core, including pirfenidone (a drug used to treat pulmonary fibrosis) ( Singh et al, 2019 ), MDB5 (a novel form of Hedgehog (Hh) inhibitor GDC-0449) ( Kumar et al, 2019 ), salinomycin (an antibiotic with anti-cancer properties) ( Sousa et al, 2019 ), and doxorubicin (an anthracycline chemotherapeutic) ( Fang et al, 2014 ; Seifi-Najmi et al, 2016 ). Multiple formulations also make use of siRNA targeting genes along the EMT pathway ( Fang et al, 2014 ; Seifi-Najmi et al, 2016 ; Li et al, 2019 ; Suresh et al, 2019 ), including one directly conjugated to PEI to form a polyplex ( Ding et al, 2018 ; Wang Y. et al, 2019 ), as well as an inhibitor of CXCR4 ( Suresh et al, 2019 ), a chemokine receptor involved in the promotion of tumor migration and EMT ( Lin et al, 2018 ).…”
Section: Nanomedicinementioning
confidence: 99%
“…These all resulted in the inhibition of key EMT-biomarkers, including PAI-1, TGF-β, VEGF, Hh, Vimentin, and N-Cadherin. This led to decreased collagen deposition ( Wang Y. et al, 2019 ; Kumar et al, 2019 ; Li et al, 2019 ), cell migration and metastasis ( Fang et al, 2014 ; Seifi-Najmi et al, 2016 ; Sousa et al, 2019 ), and tumor growth ( Suresh et al, 2019 ). Polymeric NPs increased lung penetration and retention, provided stability by a polymer-siRNA conjugate, and facilitated codelivery further enhanced API efficacies.…”
Section: Nanomedicinementioning
confidence: 99%